2020
DOI: 10.12659/msm.918207
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Inhibits Cell Proliferation and Induces Markers of Cell Senescence in CD34+CD38– Leukemia Stem Cells Derived from KG1α Acute Myeloid Leukemia Cells by Activating the Sirtuin 1 (SIRT1)/Tuberous Sclerosis Complex 2 (TSC2) Signaling Pathway

Abstract: Background: Clinical relapse in acute myeloid leukemia (AML) is associated with the reduced treatment response of leukemia stem cells (LSCs). This study aimed to investigate the effects of the ginseng derivative, ginsenoside Rg1 (Rg1), on CD34+CD38-LSCs derived from KG1a human acute myeloid leukemia cells. Material/Methods: CD34+CD38-LSCs were isolated from KG1a human acute myeloid leukemia cells by cell sorting. CD34+CD38-KG1a LSCs were divided into the control group and the Rg1 group (treated with Rg1). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Pre-labeled EV-rich fractions (75 × 10^12/mL) were incubated with PK1 cells for 48 h, and tracked to confirm engraftment. Staining for SA-Spider-ß-Gal in PK1 cells was performed as previously described [22] following manufacturer's protocol (Cat#SG04-01, Dojindo).…”
Section: In Vitro Ev Efficacymentioning
confidence: 99%
“…Pre-labeled EV-rich fractions (75 × 10^12/mL) were incubated with PK1 cells for 48 h, and tracked to confirm engraftment. Staining for SA-Spider-ß-Gal in PK1 cells was performed as previously described [22] following manufacturer's protocol (Cat#SG04-01, Dojindo).…”
Section: In Vitro Ev Efficacymentioning
confidence: 99%
“…In our previous study, using H 2 O 2 to induce human dermal fibroblasts cells to establish a cell injury model found that the expression of P16, P21, P53, and Caspase‐3 was significantly inhibited, while the signal‐regulated kinase and Akt serine/threonine kinase 1 were activated. This indicates that TFPS can reduce the oxidative stress response and apoptosis rate of model cells by up‐regulating the expression of SIRT1 11 …”
Section: Discussionmentioning
confidence: 90%
“…We found that Rg1 treatment remarkably attenuated CD34 + CD38 − LSCs proliferation and obviously decreased proliferative index (PI) by modulating cell cycle, which is consistent with the findings of previous studies. 1,28 Therefore, the Rg1 significantly inhibits the proliferation and blocks the cell cycle of CD34 + CD38 − LSCs. The previous study 29 reported that SA-β-Gal staining could reflect the senescence of CD34 + CD38 − LSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the colony formation assay was carried out as described in previous studies, with some modifications. 1,17 Briefly, the CD34 + CD38 − LSCs were seeded onto 96-well plates, cultured and incubated with methylcellulose (final concentration of 0.8%; Sigma-Aldrich) with 5% CO 2 at 37°C for 2 weeks. A total of 50 or more colony formation units (CFU) of cells were defined as 1 mixed CFU (CFU-Mix).…”
Section: Colony Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation